2014
DOI: 10.1061/(asce)ww.1943-5460.0000209
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Field Study of Swash-Zone Processes. II: Sheet Flow Sediment Concentrations during Quasi-Steady Backwash

Abstract: Sheet flow sediment concentration profiles were measured in natural conditions for the first time as part of a comprehensive field study on swash-zone hydrodynamics and sediment transport. Three conductivity concentration profilers (CCPs) measured the sediment concentration profile in the sheet flow layer with a 1 mm resolution in the swash zone of a dissipative beach. This paper focuses on sheet flow during quasi-steady backwash events generated by infragravity motion when the effects of phase lags, surface-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 66 publications
5
54
0
Order By: Relevance
“…Lanckriet et al [2014] found good agreement of (6) with field measurements in the swash zone using a 5 1.73. Integration of (5) then yields:…”
Section: Sheet Flow Layer Thicknesssupporting
confidence: 62%
See 2 more Smart Citations
“…Lanckriet et al [2014] found good agreement of (6) with field measurements in the swash zone using a 5 1.73. Integration of (5) then yields:…”
Section: Sheet Flow Layer Thicknesssupporting
confidence: 62%
“…Wilson [1987] derived (1) analytically from a force balance between the shear stress and the granular friction (based on a dynamic Coulomb yield criterion that was originally proposed by Bagnold [1956Bagnold [ , 1966) and estimated K % 10. Good agreement between (1) and measurements of (quasi-)stationary sheet flow has been observed [Sumer et al, 1996;Lanckriet et al, 2014]. Equation (1) has also been used to predict the quasi-steady and maximum sheet flow layer thickness under oscillatory flow Malarkey et al, 2003;Dong et al, 2013].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Shortly afterward, the flow evolves from subcritical to supercritical as the favorable pressure gradient becomes increasingly stronger during the backwash phase [Baldock and Hughes, 2006]. Sediment transport is then dominated by bed-generated turbulence [Longo et al, 2002;Cowen et al, 2003;Zhang and Liu, 2008;Lanckriet and Puleo, 2013] that may also mobilize sediment as sheet flow [Hughes et al, 2007;Lanckriet et al, 2014]. The relative dominance of the different flow phases (i.e., uprush versus backwash asymmetry) during a swash cycle largely depends on the beach face slope and incident wave conditions [Masselink and Puleo, 2006] and is known to have a large influence controlling the overall morphological response of the beach [Osborne and Rooker, 1999;Blenkinsopp et al, 2011;Puleo et al, 2014a;Masselink et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the mean and turbulent flow field during the different phases of an individual swash cycle under natural [Puleo et al, 2000;Butt et al, 2004;Aagaard and Hughes, 2006;Raubenheimer et al, 2004;Blenkinsopp et al, 2011;Puleo et al, 2014b;Lanckriet et al, 2014] and laboratory [Cowen et al, 2003;Barnes et al, 2009;O'Donoghue et al, 2010;Sou et al, 2010;Sou and Yeh, 2011;Kikkert et al, 2012Kikkert et al, , 2013 conditions. Moreover, recent numerical studies [e.g., Brocchini and Baldock, 2008;Bakhtyar et al, 2009;Zhu and Dodd, 2013;Torres-Freyermuth et al, 2013] have provided additional information on the dynamics in this region, as they allow improved understanding of temporal and spatial variability of flow properties under different boundary/forcing conditions.…”
Section: Introductionmentioning
confidence: 99%